2017
DOI: 10.18632/oncotarget.21606
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic stress induces transfer of mitochondria-associated human endogenous retroviral RNA and proteins between cancer cells

Abstract: About 8 % of the human genome consists of human endogenous retroviruses (HERVs), which are relicts of ancient exogenous retroviral infections incurred during evolution. Although the majority of HERVs have functional gene defects or epigenetic modifications, many of them are still able to produce retroviral proteins that have been proposed to be involved in cellular transformation and cancer development.We found that, in chemo-resistant U87RETO glioblastoma cells, cytotoxic stress induced by etoposide promotes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 70 publications
(103 reference statements)
1
34
0
1
Order By: Relevance
“…Mitochondrial transfer from donor cells to cells of injured tissues is a promising cell‐based therapy that effectively brings about the recovery of tissue bioenergetics. Syncytin‐1/syncytin‐2 also function to mediate the cell‐to‐cell transfer of mitochondria, and this could be blocked by anti‐syncytin‐1 and anti‐syncytin‐2 antibodies …”
Section: Functional Roles Of Hervs In Carcinogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial transfer from donor cells to cells of injured tissues is a promising cell‐based therapy that effectively brings about the recovery of tissue bioenergetics. Syncytin‐1/syncytin‐2 also function to mediate the cell‐to‐cell transfer of mitochondria, and this could be blocked by anti‐syncytin‐1 and anti‐syncytin‐2 antibodies …”
Section: Functional Roles Of Hervs In Carcinogenesismentioning
confidence: 99%
“…Syncytin-1/ syncytin-2 also function to mediate the cell-to-cell transfer of mitochondria, and this could be blocked by anti-syncytin-1 and antisyncytin-2 antibodies. 121 Huang et al demonstrated that Env proteins encoded by HERV-K could mediated intercellular fusion of melanoma cells, 122…”
Section: Herv-mediated Cell Fusionmentioning
confidence: 99%
“…They observed that, by simple co-incubation, chloramphenicol-(CAP s ) and efrapeptin-(EF s ) sensitive mammalian cells were able to incorporate mitochondria, purified beforehand from CAP r and EF r resistant cells [97]. Ever since, many cells have been reported to undergo mitochondrial transformation [55,[98][99][100][101][102]. This process is believed to occur via macropinocytosis.…”
Section: Transfer Of Free Mitochondriamentioning
confidence: 99%
“…Серед факторів, які зумовлюють таку регуляцію, можуть бути малі інтерферуючі РНК і альтернативний сплайсинг, який спричиняє продукцію ізоформи протеїну, що не впізнається комерційними антитілами. Синцитин-1 був виявлений для клітин U87 Dнaz-Carballo D. та співавторами [13], проте його продукція у ракових клітинах може бути причиною дезрегуляції на рівні транскрипції у результаті активації вутрішнього промотора. Таким чином, для вивчення регуляції експресії цих генів на рівні РНК і виявлення альтернативних ізоформ транскриптів цих генів ми обрали стратегію аналізу за допомогою праймерів до різних ділянок генів.…”
Section: матеріали і методиunclassified